DYNAMICS BETWEEN SPIRITUALITY, LEADERSHIP AND LIFE GOALS: - G.E. Dames (Acta Theologica)
In this article the relation between school leadership, spirituality, and ultimate life goals is considered. The objective of the study is to explore how leadership and spirituality are related and informed by ultimate life goals in schools. Spirituality is defined as a way of life of growing into human fullness that is grounded in a moral universe. Ultimate life goals represent ultimate values in the life of leaders and their deepest motivation for decisions and actions. Ultimate life goals originate from our contingent nature – as we move or change, we are constantly in need of a grounding/foundation. It gives direction and meaning in change and form through spiritual transformation. The life narrative research methodology was applied to explore the ultimate life goals and spiritual transformation in the life narratives of seven school principals in Roman Catholic private schools in Gauteng and two public schools in the Western Cape.